AN ANALYSIS OF TURN TAKING STRATEGIES USED BY LECTURERS AND STUDENTS THROUGH ONLINE CLASS - Silitonga, Maria Elizabet; Pasaribu, Arsen; Sinambela, Erika (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
This study deals with turn taking strategies. The study aims to investigate the types of turn taking strategies used by lecturers ans students, to find out how turn taking strategy realized and to identify the dominant types used by lecturers and students. This studey uses descriptive qualitative research design which employed two data collection techniques, i.e. observation and video recording. The number of data that containing types of turn taking strategy is 200 data. The data are, then, analyzed by using theory from Strenstrom (2001). Techniques of analyzing data is by classifying the data based on their types, then the data will be count in each category to make the analysis more comprehensive by knowing which category ranks the highest and vice versa. Finally the result will be put in findings. The results of the research indicates that: the dominant type used by lecturers in semantics class, kajian budaya and technology of translation, are prompting strategy, meanwhile in akustik dan organologi class, the lecturer used taking over and prompting strategy as the dominant types. Meanwhile the students used the same dominant types in four different class, they are taking over strategy. While the types that is not used at all in four different classes are the silent pause strategy and giving up strategy.